A green protocol for one pot synthesis of benzosuberone tethered thiadiazolopyrimidine-6-carboxylates using PEG-400 as potent anti-proliferative agents. Issue 31 (1st August 2018) - Kasaboina, Suresh; Bollu, Rajitha; Gomedhika, P. Mary; Ramineni, Venkatesh; Nagarapu, Lingaiah; Dumala, Naresh; Grover, Paramjit; Nanubolu, Jagadeesh Babu
Graphical abstract: Design strategy for 2, 3-dimethylbenzocycloheptenone tethered thiadiazolo-pyrimidine carboxylates (8a–k ). Highlights: Newly synthesized benzosuberone tethered thiadiazolo-pyrimidine carboxylates. Evaluated for their in vitro anti-proliferative activity against four human cell lines. Compound8k showed the most promising activity against all the cell lines. First report on the synthesis using PEG-400 and in vitro anti-proliferative evaluation. Abstract: A new concise and facile method was explored to synthesize a collection of new benzosuberone based thiadiazolo [3, 2- a ] pyrimidine-6-carboxylates using polyethylene glycol (PEG), which could be regarded as the derivatives of the hybrid scaffolds of bioactive natural benzosuberone and heterocyclic thiadiazolo[3, 2- a ]pyrimidine. The structures of the synthesized compounds were characterized by 1 H, 13 C NMR, MS and IR; and their anti-proliferative activity was evaluated against four human cancer cell lines; A549, SKNSH, HeLa and MCF-7. Among the tested compounds, compound8k showed the most prominent activity against all the cell lines and these results may lay the foundation for further design of novel anti-proliferative agents.